A carbon nanotube/poly [Ni-(Protoporphyrin IX)] composite for amperometric detection of long chain aliphatic amines - Gravielle, Maria Clara (2015)
Poly [Ni-Protoporphyrin] film (pNiPP), containing multiwall carbon nanotubes (MWCNT) was used to cover a glassy carbon electrode. The hybrid material (pNiPP/MWCNT) successfully combines the permselectivity of pNiPP with the high conductivity of MWCNT.The modified electrode was used to perform amperometric detection of long chain aliphatic amines (LCAA) in order to prevent the passivation effect of the aliphatic chain. Cyclic voltammetry (CV) and electrochemical impedance spectroscopy (EIS) demonstrated that the pNiPP/MWCNT facilitates the electron transfer reaction. The charge transfer resistance (Rct) values were significantly lower by up to one order of magnitude compared to the bare electrode. Differential pulse polarography (DPP) showed a marked decrease of the overpotential generated by the aliphatic chain. The calibration of the amperometric peak area vs. concentrations of derivatized LCAA exhibits a linear response within the range of 0.018 and 28μM and correlation coefficient (R2) higher than 0.999 (n=5). The quantitation limit of the pNiPP/MWCNT electrode is about 400 times lower than the UV-visible detection. RSD of 7.2%, 5.8%, 2.5% and 2.3% was obtained for concentrations of 0.028, 0.28, 2.8 and 28μM of ferrocenyl octadecylamine. A solution of sphingosine, 0.23μM, was exclusively detected with HPLC-ECD with pNiPP/MWCNT electrode.